KNOWLEDGE, ATTITUDE, AND BEHAVIOUR TOWARDS THE EFFORTS OF DENTAL CARE AND MOUTH CARE FOR STUDENTS OF ELEMENTARY SCHOOLS OF SEMBUNG VILLAGE IN 2011 - I Wayan Suanda; Ni Nengah Sumerti (Jurnal Kesehatan Gigi (Dental Health Journal), 2014)
Prevention of the oral disease, including dental caries is determined by three factors : predispotition factor, including knowledge, attitude, and skills in oral health care, support factor, incLuding equipment, tools and facilities of health care, and reinforcement factor, including community support, religions leaders and health professionals.The study is cross sectional study with descriptive quantitative design with the objective to understand the knowledge, attitude and behaviour of sixth years students of Elementary Schools in Sembung Village for the eforts in dental and oral care. This study was done in April until May 201I with 57 respondents.The result of this studyt shows that the majority of the respondents hove knowledge level of dental an oral care efforts with a category of average (57.9%), the attitude of the respondents towards the efforts of dental care is good in general, and there is no to have below average in attitude. The behaviours below average (38.69%) and poor (31.6%), the dental and oral hygiene of the respondents is generaly at an average of 3.25% (poor), and 56.1% suffers from caries. This study shows amalgamations of only 2 teeth.From the result of this study, it is suggested that health profesionals need to improve the frequency of the educational sessions on dental caries and simulations on the right way of brusshing teeth, organize